Development Analysis Of Banana Chips Products Using Quality Function Deployment (QFD) MethodIn The Household Industry Pilar Rejeki Kendari City - Hendri Hendri; Muhammad Syukri; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This study aims to determine the quality development of banana chips using the QFD method in the Pillar Fortune Home Industry. Determination of the research location purposively. Data was collected using a questionnaire, interview, and documentation methods. The analytical method used is Quality Function Deployment (QFD). The results showed that the development of banana chips products using the QFD method to the priority to be developed by the wishes and needs of consumers in a row, among others: (1) Does not contain harmful chemicals (9.22%), (2) Tastes good ( 8.76%), (3) Competitive price with other products (8.75%), (4) There is a PIRT/BPOM RI permit number on the packaging (8.37%), (5) Does not contain preservatives (8, 29%), (6) Complete ingredient composition (8.00%), (7) Price according to taste and delicacy (7.62%), (8) Affordable price for all people (7.60%), (9 ) Expiration date (7.10%), (10) Attractive packaging design (6.61%), (11) Crispy crunchy texture (7.04%), (12) Many flavors (6.34%), ( 13) Attractive colors (6.29%). Technical requirements or technical responses from companies to meet consumer wants and needs start from the processing process that begins with sorting bananas, washing/cleaning processes, slicing processes, frying processes, adding flavorings, packaging or labels, making more attractive packaging designs, the inclusion of the price of banana chips, the inclusion of the composition of banana chips ingredients, increasing product promotion, and creating a marketing system.